2017
DOI: 10.1038/s41598-017-05831-x
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable hexafunctional anion receptor with operational urea-based inner cleft and thiourea-based outer cleft: Novel design with high-efficiency for sulfate binding

Abstract: The recognition of anions by designed receptors has attracted much attention in recent days. In particular, the selective binding of sulfate with artificial receptors is important because of its relevance to many biological and environmental applications. However, the development of organized molecular receptors with high-efficiency for sulfate binding still remains a significant challenge. We report a novel para-phenylene-bridged hexafunctional tripodal receptor that contains a urea-based inner cleft and a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 54 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…To assess the effect of different glycosidic bond angles (Rassolov et al 2001;Zhao and Truhlar 2008) in Gaussian 09 (Frisch et al 2010), a reliable method that has been applied constantly to obtain reasonable molecular structures for organic molecules (Fradon et al 2017;Khansari et al 2017;Zhao and Truhlar 2008;Zhou et al 2017). Forty-nine cellulose tetramer chain conformations with different U/W angles were generated for each C6 conformers (gg: C4-C5-C6-O6 = 57.2°; gt: C4-C5-C6-O6 = 178.1°; tg: C4-C5-C6-O6 = 285.7°).…”
Section: Methodsmentioning
confidence: 99%
“…To assess the effect of different glycosidic bond angles (Rassolov et al 2001;Zhao and Truhlar 2008) in Gaussian 09 (Frisch et al 2010), a reliable method that has been applied constantly to obtain reasonable molecular structures for organic molecules (Fradon et al 2017;Khansari et al 2017;Zhao and Truhlar 2008;Zhou et al 2017). Forty-nine cellulose tetramer chain conformations with different U/W angles were generated for each C6 conformers (gg: C4-C5-C6-O6 = 57.2°; gt: C4-C5-C6-O6 = 178.1°; tg: C4-C5-C6-O6 = 285.7°).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, there is a growing interest in designing artificial receptors that can selectively recognize anions and act as sensors 2 , 3 . A wide variety of host receptors have been reported that can effectively bind anions in solution and in the solid states, exhibiting selectivity toward certain anions 4 7 . In this regard, carboxylates are of great interest due to their important roles in chemistry and biology 8 10 .…”
Section: Introductionmentioning
confidence: 99%
“… 17 23 In particular, the electron-withdrawing nature of sulfur on thiourea functionalities increases the acidity of NH for H-bonding interactions with an anionic guest. 23 For example, a chlorosubstituted tris(thiourea) receptor reported by Das et al was shown to encapsulate a thiosulfate anion with a dimeric capsular assembly. 20 A tris(4-nitrophenyl)thiourea receptor was reported to exhibit selective complexation of fluoride and phosphate.…”
Section: Introductionmentioning
confidence: 99%